Penerapan Model Problem Based Learning dalam Meningkatkan Minat Membaca Siswa Kelas II Sekolah Dasar - Muhammad Riski; Tri Wintolo Apoko (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to find out whether the problem-based learning model can stimulate elementary school students' interest in learning Indonesian by helping them to read in the classroom. This study used an experimental method. Students from SDN Dukuh 04 Pagi who were in the second grade participated in this study. They were divided into two groups: an experimental group and a control group. The problem-based learning paradigm is the independent variable in this study, while the reading interest of third grade elementary school students learning Indonesian is the dependent variable. This research was conducted by collecting numerical information or information consisting of all words or sentences, then converting them into numerical information. information collection strategies used questionnaires. Normality test, homogeneity test, and hypothesis test are data analysis procedures from both descriptive and inferential statistical analysis. The results of the independent t-test showed that the t-value was 5.608 and the two-sided significance value (2 tailed) was 0.00. According to the findings of this study, students' reading comprehension and their level of interest in primary education can be improved by problem-based learning.